Investigation of Hydrological, physicochemical parameters, the level of fouling and metal corrosion rate in seawater environment at Long Son areas of Ba Ria – Vung Tau province - Pham, Hồng Thạch; Nguyen Van, Sơn; Pham, Thanh Hải; Nguyen Trong, Cường; Tran, Phương Chiến; Nguyen Van, Dũng; Le Thi, Thùy Nguyên; Lam, Ngọc Nam (Journal of Military Science and Technology, 2022)
This article presents the results of determining the hydrophysical and chemical parameters, the degree of fouling, and the corrosion rate of carbon steel, copper, aluminum, and zinc in the water in the wharf area of the 2nd Naval Region M/BTL Brigade stationed in Ba Ria - Vung Tau province. The measurement results reached the hydrochemical parameters, the salinity of 18.4 ppt, pH = 6.9, the temperature of 29.2 oC, and conductivity of 30.6 mS/Cm, TDS 15.5 g/L; The level of fouling showed that the aluminum sample had the highest level and included seaweed, the carbon steel sample had a very high fouling density, and the zinc and copper samples had a low density. Corrosion rate results show that carbon steel 218 ± 8.72 μm/year, copper 93 ± 4.46 μm/year, zinc 79 ± 3.16 μm/year, and aluminum 9 ± 0.42 μm/year. In particular, the copper sample has severe localized corrosion at the edges of the immersed specimens.